EFFICIENCY OF INTEGRATION OF HIGHER AND SECONDARY EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Higher and secondary education should always be two systems connected to each other. This article discusses the integration and joint operation of these two systems.